Dental prosthesis ingested and impacted in the esophagus and orolaryngopharynx - Abdullah, B.J.J.; Teong, L.K.; Mahadevan, J.; Jalaludin, A. (1998)
Objective: Impacted foreign bodies in the trachea and esophagus are common. In the esophagus, these are usually bones, while for the trachea, it is commonly some form of seed or nut. The incidence of impacted dental prostheses is not highlighted in the literature. They usually have a definite history of ingestion, frequently during trauma, seizures, or Sleep. Prompt management in a safe and effective manner is required if significant morbidity, and even mortality, is to be avoided. Method: The records of all patients who presented to the University Hospital in Kuala Lumpur with a definite history of foreign-body ingestion in the form of a dental prosthesis were reviewed, and their respective radiographs reassessed. Results: There were 21 patients with impacted dental prostheses from a total of 200 patients who had impacted foreign bodies (11.5). Indirect laryngoscopy detected five of these dentures, and in only seven were the dentures seen on plain radiography (33)-all of which had metal wires attached. Of the 21 patients, 16 had the foreign bodies removed endoscopically; 2 could not be removed and were allowed to pass through the gastrointestinal tract under close monitoring; and 3 whose dental prostheses were not detected and who subsequently passed the foreign bodies. Conclusions: Impacted dental prostheses appear to constitute a significant proportion of impacted foreign bodies in the orolaryngopharynx. The majority are radiolucent. In the presence of positive history or/and symptoms, endoscopic examination and removal is suggested if possible to reduce morbidity. No serious complications have been seen.